Learning Styles and Outcomes of Students with Intellectual Disabilities Using E-LAPD on Mole Concept: A Mixed Methods Study - Shinta Dian Pramesty; Soekarmiani; Moniqsa Purbo Syahrani; Ima Kurrotun Ainin; Dian Novita (JTP - Jurnal Teknologi Pendidikan, 2025)
The characteristics of students with intellectual disabilities who have difficulty processing information require innovation and the use of learning media that are specifically designed for students with intellectual disabilities. However, innovation and the use of learning media, especially E-LAPD , are still very limited. This study analyzes the learning styles and outcomes of students with intellectual disabilities in understanding the mole concept material through the use of E-LAPD for individual learning. The study uses mixed method design with a type of concurrent embedded design, which both quantitative and qualitative data are collected simultaneously. Three students with intellectual disabilities in SMAN 10 Surabaya as research subjects. Data collection through interviews and pretest-posttest questions. The results of the interview were analyzed using NVivo 11 software in the form of matrix query coding. Quantitative data analysis uses descriptive statistics by comparing the pretest and posttest scores of each student. The research results indicated that the learning styles frequency of students with intellectual disabilities is a visual learning style. Pretest and posttest results significantly increase, indicating increased learning outcomes. The use of E-LAPD can simplify chemical concepts into visual information, so as to improve the learning outcomes of students with intellectual disabilities.